Subarachnoid Hemorrhage due to Ruptured Anterior Communicating Artery Aneurysm in a Child with Coarctation of Aorta (Journal of Nobel Medical College, 2022)
Intracranial aneurysms are sometimes associated with other vascular anomalies in extracranial location. Coarctation of aorta, a congenital vascular lesion can be associated with intracranial aneurysms. In patients with coarctation, evaluation of intracranial vasculature is essential. We encountered a 12-year kid with subarachnoid hemorrhage. On further evaluation, she had anterior communicating artery aneurysm. On further evaluation for secondary causes of aneurysm, she had coarctation of aorta. She was surgically managed successfully by clipping of the aneurysm.